Ambient Vibration Test of a Prestressed Concrete Box Girder Bridge - Montalto Bolaños, Eduardo José (2017)
This paper presents the results of an off-line vibration based monitoring of a simply-supported, prestressed concrete box girder bridge. The structure evaluated was the Tenorio River Bridge in National Route 1, Costa Rica, which was built in 2014. The purpose of the study was to register the dynamic response of the bridge under operational conditions and to identify its vibration modes using the covariance driven stochastic subspace identification method (SSI – COV). The ambient vibration test was carried out using a hybrid monitoring system developed by LanammeUCR. Uniaxial accelerometers were used to register the accelerations at 25 different locations on the bridge for approximately 40 minutes. Through the analysis of the data, nine vibration modes were identified in the frequency range of 0 to 25 Hz, including vertical bending modes, torsional modes and one transverse bending mode.